Udział duchowieństwa rzymskokatolickiego diecezji kieleckiej w kampanii wyborczej Stronnictwa Narodowego w wyborach 1930 roku - Ospara, Łukasz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
Udział duchowieństwa katolickiego diecezji kieleckiej w kampanii wyborczej Stronnictwa Narodowego, podczas wyborów parlamentarnych w roku 1930 przybierał różne formy. Jedynym kandydatem do Sejmu z listy SN był ksiądz Adam Błaszczyk z Kielc. Jego działalność w partii, a także propagowanie SN wśród mieszkańców diecezji wspierał ksiądz Antoni Sobczyński. Duża część duchowieństwa organizowała spotkania agitacyjne dla potencjalnych wyborców oraz udostępniała plebanie dla polityka SN. Największe poparcie politycy SN otrzymali w dniu wyborów 16 listopada 1930, kiedy to większość księży diecezji namawiała wyborców do głosowania na SN, wykorzystując do tego celu ambonę. Duchowni tego dnia zamiast kazania propagowali SN jako jedyną partię broniącą katolicyzmu w Polsce.

Roman Catholic Clergy from the Diocese of Kielce campaigned for the National Party during the 1930 parliamentary elections in a variety of ways. The Reverend Adam Blaszczyk from Kielce was one of the candidates to become a Member of Parliament. His political activities, namely, agitation for the National Party among inhabitants of the diocese, were endorsed by the Reverend Antoni Sobczynski. The vast majority of the Catholic Clergy organized political meetings aimed at recruiting potential voters. They also made use of buildings belonging to the Church such as presbyteries or they made churchyards available for the National Party’s politicians. The greatest endorsement from Roman Catholic Clergy came on the Election Day – November 16th 1930, when the majority of priests agitated from the pulpit for voting for the National Party. Instead of giving sermons, priests were campaigning for the National Party hailing it as the only defender of the Catholic Church in Poland.
Keywords: Stronnictwo Narodowe; diecezja kielecka; Kościół katolicki; wybory 1930; duchowieństwo rzymskokatolickie; National Party; Diocese of Kielce; Catholic Church; 1930 Polish parliamentary elections; Roman Catholic Clergy